Efficiency of PEG secondary concentration and PCR for the simultaneous concentration and quantification of foodborne bacteria, viruses and protozoa. Issue 10 (21st May 2020) - Monteiro, Silvia; Smigic, Nada; Rajkovic, Andreja; Santos, Ricardo
ABSTRACT: Fresh fruits are a potential source of many different pathogens, including bacteria, enteric viruses and protozoa that may pose serious health risks. The consumption of raspberries has been widely associated with large foodborne outbreaks and because of the low concentration at which most of these pathogens are found, sensitive and accurate detection methods are required. Methods that would allow for an accurate and sensitive simultaneous elution and concentration of the different classes of pathogens would decrease the time for analysis, the costs associated and the expertise necessary. In this study we explored the use of polyethylene glycol (PEG) secondary concentration to simultaneously concentrate bacteria, enteric viruses and protozoa from raspberries. PEG secondary concentration showed good recovery rates for all the organisms tested. This work indicates that PEG secondary concentration followed by quantitative (Reverse Transcription) Polymerase Chain Reaction (q(RT)PCR) may be a relevant alternative to standardized methods for the simultaneous concentration of bacteria, enteric viruses and protozoa. Abstract : Simultaneous detection of bacteria, viruses and protozoa in raspberries.